Environmental ethics and natural resources’ management: understanding the basis of economic issues - Arbulú Villanueva, Italo (2013)
The discussion about this global framework of rights and duties, between humans and other living things and nonliving things, has given rise to a fascinating body of literature in the field of ethics that has been called environmental ethics. The aim of this paper is twofold, first it seeks to present the current elements in the field of environmental politics governing the definition of economic policies on the use of environment and natural resources. Second, it suggests the appearance of other thinking that can influence the way society evaluates the human-nature relationship.